Bacterial infections in patients with COVID-19 admitted to an adult ICU: incidence and pharmaceutical performance - Kauanna OLIVEIRA; Deisy FILIPAK; Karina da Silva AGUIAR; Marcela Bechara CARNEIRO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: The present study aimed to determine the incidence of bacterial infection in patients infected with SARS-COV-2 admitted to intensive care units (ICUs) of an oncological hospital in southern Brazil and to demonstrate the role of the pharmacist in the management of antimicrobials. Methods: In this descriptive and retrospective observational study, all patients with COVID-19 confirmed by polymerase chain reaction (PCR) examination, admitted to adult ICUs at Erasto Gaertner Hospital from May 2020 to August 2021 were included, and demographic and clinical data were evaluated through medical records, in addition to the number and classification of pharmaceutical measures. Results: Of 192 patients hospitalized with COVID-19 in the ICU, 104 (54%) had an oncological diagnosis, 62 (60%) with solid cancer and 42 (40%) with hematological diagnosis. Regarding the length of hospital stay, the patients were hospitalized for an average of 9.5 days (SD:6.4), treated with invasive procedures. Of these, 44 (23%) had ventilator-associated pneumonia (VAP) and 32 (17%) patients developed a bloodstream infection (BSI). The most prevalent bacteria were Acinetobacter baumannii with a multiresistant profile and methicillin-sensitive Staphylococcus aureus. Sixty pharmaceutical measures were taken to manage the use of antimicrobials, the most prevalent being: addition, discontinuity, de-escalation, calculation and dose adjustment. With regard to clinical outcome, 147 (77%) of patients hospitalized with COVID-19 died. As for the co-infected patients, 36 (82%) of the patients with VAP and 28 (88%) with ICS died. Conclusions: The results obtained were consistent with the literature, in which the rates of co-infection and use of antimicrobials were high. In addition, pharmaceutical interventions demonstrate the importance of this professional in patient care and in the multidisciplinary team regarding the rational use of antimicrobials.